The Roads and Bridges in the Early History of Scotland - Inglis, Harry R G (Proceedings of the Society of Antiquaries of Scotland, 1913)
Up to the fifteenth century the movements of all the chief expeditions in Scotland seem to have been across open country, and it was only the erection of bridges in the fifteenth, sixteenth, and seventeenth centuries that made definite the lines of traffic, which afterwards gradually developed into roads. The structures are considered under the following headings: early literature and documents, comparative chronology and chief pre-Reformation bridges (mainly Stirling and Perth).